Low Cost Technology, a Vision on Agricultural Research for Farmers - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Remarkable research advancement and break-through have been achieved in various disciplines of research including breeding, genetics, physiology, plant protection, finally up to molecular biology to produce high yielding crop cultivars. Of course, biotechnologist made innovative progress in the production of insect resistant Bt-crop cultivars but recently it failed to give good results in farmers fields. Recently, there was a lot of arguments in favour or against it among specialists in linkedin team members. However, all these high technology crops can perform well under high input situations, but fail to give reasonable yield under sustainable agriculture in farmers’ fields. A gradual increase in global warming, heat stress, drought, salinity and other abiotic stresses affect crop yield substantially. It may mentioned here that about 1/3rd of the World arable land is semi-arid and 2/3rd of it is saline, thereby affecting crop productivity substantially in these areas. Very Little research inputs have been directed to improve crop productivity under sustainable agriculture. This urges a new visión in the direction of agricultural research in terms of low input but high responsive agriculture.